2009
DOI: 10.1371/journal.pone.0006216
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography and Virulence of Staphylococcus aureus

Abstract: Background Staphylococcus aureus is commonly carried asymptomatically in the human anterior nares and occasionally enters the bloodstream to cause invasive disease. Much of the global diversity of S. aureus remains uncharacterised, and is not clear how disease propensity varies between strains, and between host populations.MethodologyWe compared 147 isolates recovered from five kindergartens in Chengdu, China, with 51 isolates contemporaneously recovered from cases of pediatric infection from the main hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 46 publications
3
35
2
1
Order By: Relevance
“…The prevalence rate of PVL among the S. aureus clinical isolates tested in our study was 10.2 %, similar to that found in previous studies carried out in China and outside Shanghai (Yu et al, 2008). However, this rate was much lower than that reported previously for isolates recovered from a Chinese paediatric hospital (Fan et al, 2009). A low (1/49) rate of PVLpositive MRSA isolates was found in our study; in contrast, the proportion of PVL among MSSA isolates in our study was higher than reported previously (Chen et al, 2010).…”
Section: Discussioncontrasting
confidence: 91%
“…The prevalence rate of PVL among the S. aureus clinical isolates tested in our study was 10.2 %, similar to that found in previous studies carried out in China and outside Shanghai (Yu et al, 2008). However, this rate was much lower than that reported previously for isolates recovered from a Chinese paediatric hospital (Fan et al, 2009). A low (1/49) rate of PVLpositive MRSA isolates was found in our study; in contrast, the proportion of PVL among MSSA isolates in our study was higher than reported previously (Chen et al, 2010).…”
Section: Discussioncontrasting
confidence: 91%
“…Melles et al, investigating a large group of children and elderly adults from the Netherlands, found that CC30 and CC45 contained almost half (47.3%) of all the nasal S. aureus isolates, but CC15 was not prominent in that population (18). A Chinese study with 147 isolates from colonized children in kindergartens found that CC121 was the most prominent (34.0%), while CC30 accounted for only 3.4% of the isolates, and CC45 was not present at all (8). In a study from Mali, CC15 and CC152 together comprised 52.3% of the nasal S. aureus isolates (27).…”
Section: Discussionmentioning
confidence: 99%
“…The ST121 lineage was also the predominant lineage found in MSSA isolates through Europe and Russia [23][24][25] and an identical scenario has been reported among Asiatic children in both carriage and disease isolates, and frequently associated to PVL. Of major concern was the local emergence of methicillin resistance in ST121 isolates in these pediatric communities: one MRSA isolate, PVLnegative responsible for staphylococcal scalded skin syndrome in China and two MRSA, PVL-positive, SCCmec type V isolates responsible for osteomyelitis and soft tissue abscess in Cambodia [26,27]. Moreover, single ST121 MRSA isolates were reported in China (http://saureus.mlst.…”
mentioning
confidence: 99%